ANALISIS KESADARAN WAJIB PAJAK DAN KONTRIBUSI PAJAK DI SEKTOR HOTEL DAN RESTORAN TERHADAP PENDAPATAN ASLI DAERAH KOTA SERANG - Susilo, Aprian; Ulupui , I Gusti Ketut Agung; Perdana , Petrolis Nusa (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
Tax is a manifestation of the direct participation of the community or taxpayers in fulfilling tax obligations necessary for state financing. This research aims to identify taxpayer awareness and determine the extent of the contribution of hotel taxes and restaurant taxes to Local Revenue in Serang City. The research approach used in this study is quantitative, which focuses on numerical measurement and data analysis using descriptive analysis methods. Data collection techniques were carried out through literature study, interviews, and documentation. From the results of the analysis of the contribution to Local Revenue, it can be concluded that the realization of hotel and restaurant taxes in Serang City from 2019 to 2023 has a very low contribution category to the Local Revenue of Serang City.